Addressing Security and Architecture Through Proposing Innovative Conceptual Idea On Landed Housing Windows - Mohd Rodzi, Khairul Asyraf; Osman, Mohd Soffian; M Mohd Siraj, Suhailah (International Journal of Integrated Engineering, 2023)
Metal grill for housing windows that is fixed to the wall is commonly used in most of the residential houses in Malaysia. Due to high numbers of burglary cases reported across the country in a year, the feature seems desperately needed. However, the window grill creates a dispute, especially on the emergency exit, building façade, and opportunity to view surrounding outside. Through survey and input from the respondents, the purpose of the research is to propose an innovative idea on housing window that able to address both security and architecture aspects. Understanding behavior of typical housing residents, residents’ perception on window grill, and modus operandi of a burglar are important to ensure the innovation able to minimize the burglary ideation, without compromising the feature’s purpose as a housing window. Inspired by French windows of a traditional Malay kampong house, the design is improvised to correlate with the current context. In this research, the housing typology that is focused on is landed house, which may include bungalow, terrace, semi-detached, and townhouse.